Osteochondroma in Distal Phalanx of the Hallux. A Surgical Resolution of Two Clinical Cases - Martí Serrano, Joan; Lladó Vidal, Melcio (Revista Internacional de Ciencias Podológicas, 2010)
This study presents two clinical cases where we expose the advantages and disadvantages of excisional surgical approach of osteochondroma through lateral-distal incision of the hallux. This surgical approach is based on the collateral vascularisation of hallux and is different from the classic "fish.mounth incision".The goal is to decrease the chance of ischemia and/or postoperative infection that with the classical technique.
Keywords: ischaemia; lateral-distal incision; osteochondroma; patological anatomy